Morphometric Anatomical Points of Fruit Fly (Bactrocera dorsalis Complex) using Generalized Procrustes Analysis Model - Alyaminy, Ishmah Humaidatul Aminah Zaim; Ihwan, Khaerul; Risfianty, Dwi Kartika; Atika, Baiq Naili Dewi; Sanuriza, Irna Il; Husain, Pahmi; Ihsan, Muhammad Shohibul; Jayadi, Irfan (Jurnal Biologi Tropis, 2024)
This study aims to analyze the morphometric anatomical wings of the fruit fly Bactrocera dorsalis Complex. The species used in this study consisted of 11 (eleven) species. The analysis technique of the wings of Bactrocera dorsalis Complex, i.e. the right wing of each individual was analyzed using Morphometric landmarks with 15 anatomical points. Digital images of wings are scaled in size and scale using Adobe Photoshop CS3 software. The results of anatomical point digitization are processed into MorphoJ software v. 1.06b. Digitization data of anatomical points of wing shape was collected using Generalized Procrustes Analysis (GPA).  The results of the Canonical Variate Analysis (CVA) showed that there was a grouping of each species. The grouping of Bactrocera dorsalis complex wing types is based on the similarity of the percentage of cumulative values of CVA1 and CVA2 tests. Groups B. carambolae, B. minuscula, B. occipitalis, B. papayae, B. floresiae, B. philippinennsis, Bactrocera sp. 23, Bactrocera sp. 25, and Bactrocera sp. 26 grouped because they have similarities in wing venation. The difference in wing venation is found in Bactrocera sp. 27 and B. sumbawaensis because they are far from the group B. carambolae, B. minuscula, B. occipitalis, B. papayae, B. floresiae, B. philippinennsis, Bactrocera sp. 23, Bactrocera sp. 25, and Bactrocera sp. 26.